Teacher Preparation Programs, Partnerships, and the New Landscape for the Profession : The Time for Change Is Now - Frumkin, Rhoda; Gold, Paul; Gonzalez, Katia (Educational Research E-Books Online, Collection 2024., 2024)
In this book, readers will have the opportunity to reflect on the multidisciplinary ideas and experiences presented by higher education and PreK-12 leaders seeking to establish effective partnerships in order to impact collaboration, opportunities for innovation, and growth. Authors explored how identifying, nurturing, and sustaining partnerships in systematic and structured ways is not a one size fits all experience. Partnership development requires flexibility and ongoing engagement with stakeholders. The impact of individualization, access to resources and support systems, and the value of multiple perspectives and experiences is also shared. Each chapter ends with reflective questions to support further reflection on experiences and ideas presented. Contributors are: Louis Bruschi, Eileen Corigliano, Jane DeFazio, Lorrie DeSena, Jose Luis Diaz Jr., David Gordon, Josephine Marcantonio, Dina Prisco, Vannessa Smith-Washington, Patricia Tooker and Joao Arnaldo Vembane.